Oral health behaviours of older Australian men: the Concord Health and Ageing in Men Project. (9th May 2019) - Tran, J; Wright, FAC; Takara, S; Shu, C‐C; Chu, SK‐Y; Naganathan, V; Hirani, V; Blyth, FM; Le Couteur, DG; Waite, LM; Handelsman, DJ; Seibel, MJ; et al.
Abstract: Background: The Concord Health and Ageing in Men Project (CHAMP) is a cohort study of the health of a representative sample of older Australian men. The aim of this paper is to describe the oral health behaviours and dental service use of CHAMP participants and explore associations between oral health behaviours with and general health status. Method: Information collected related to socio‐demographics, general health, oral health service‐use and oral health behaviours. Key general health conditions were ascertained from the health questionnaire and included physical capacity and cognitive status. Results: Fifty‐seven percent of the men reported visiting a dental provider at least once or more a year and 56.7% did so for a "dental check‐up". Of those with some natural teeth, 59.3% claimed to brush their teeth at least twice or more a day. Most men (96%) used a standard fluoride toothpaste. Few participants used dental floss, tooth picks or mouth‐rinses to supplement oral hygiene. Cognitive status and self‐rated general health were associated with dental visiting patterns and toothbrushing behaviour. Conclusions: Most older men in CHAMP perform favourable oral health behaviours. Smoking behaviour is associated with less favourable dental visiting patterns, and cognitive status with toothbrushing behaviour.